Comparison Of Hydrological Homogenization Methods For Development Of Flood Regional Models - Abdolhay, Atefeh (2008)
Water resource management, design of hydraulic structures such as bridges, dams, roads and railways, land use management and flood control depend on reliable estimates of flood with various risk of exceedance. Lack of funds and human resources in many developing countries such as Iran have resulted in limited climatological and hydrological data. Regional flood frequency analysis (RFFA) is used for characterization of flood in ungauged location with the support of gauged sites in areas of similar hydrological characteristics. Gorganrood basin is one of the areas which are exposed to frequent floods. Due to insufficient hydrometric stations in this area direct prediction of flood is not applicable. In order to apply RFFA to study area parameters such as NDVI, curvature, area, mean slope of basin and etc were estimated for each subbasin.